A gene-centric analysis of activated partial thromboplastin time and activated protein C resistance using the HumanCVD focused genotyping array - Gaunt, Tom R (Nature Publishing Group, 2013)
Activated partial thromboplastin time (aPTT) is an important routine measure of intrinsic blood coagulation. Addition of activated protein C (APC) to the aPTT test to produce a ratio, provides one measure of APC resistance. The associations of some genetic mutations (eg, factor V Leiden) with these measures are established, but associations of other genetic variations remain to be established. The objective of this work was to test for association between genetic variants and blood coagulation using a high-density genotyping array. Genetic association with aPTT and APC resistance was analysed using a focused genotyping array that tests approximately 50 000 single-nucleotide polymorphisms (SNPs) in nearly 2000 cardiovascular candidate genes, including coagulation pathway genes. Analyses were conducted on 2544 European origin women from the British Women's Heart and Health Study. We confirm associations with aPTT at the coagulation factor XII (F12)/G protein-coupled receptor kinase 6 (GRK6) and kininogen 1 (KNG1)/histidine-rich glycoprotein (HRG) loci, and identify novel SNPs at the ABO locus and novel locus kallikrein B (KLKB1)/F11. In addition, we confirm association between APC resistance and factor V Leiden mutation, and identify novel SNP associations with APC resistance in the HRG and F5/solute carrier family 19 member 2 (SLC19A2) regions. In conclusion, variation at several genetic loci influences intrinsic blood coagulation as measured by both aPTT and APC resistance.